2010
DOI: 10.1203/pdr.0b013e3181c0b200
|View full text |Cite|
|
Sign up to set email alerts
|

A 3-D Well-Differentiated Model of Pediatric Bronchial Epithelium Demonstrates Unstimulated Morphological Differences Between Asthmatic and Nonasthmatic Cells

Abstract: There is a need for reproducible and effective models of pediatric bronchial epithelium to study disease states such as asthma. We aimed to develop, characterize, and differentiate an effective, an efficient, and a reliable three-dimensional model of pediatric bronchial epithelium to test the hypothesis that children with asthma differ in their epithelial morphologic phenotype when compared with nonasthmatic children. Primary cell cultures from both asthmatic and nonasthmatic children were grown and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 19 publications
9
81
2
Order By: Relevance
“…Although the HBE cells used in this study were from subjects without lung disease, it has been reported that bronchial epithelial cell cultures from subjects with asthma contain many more goblet cells and fewer ciliated cells compared with those from healthy subjects. 28 Conclusions Th e fi ndings in the current study suggest that sPLA 2 are released from ciliated airway epithelial cells and act on goblet cells in a paracrine manner to stimulate LTB 4 , LTC 4 , and MUC5AC secretion. We reported previously that IL-33 acts directly on goblet-enriched cells, but not ciliated-enriched cells, to stimulate IL-8 production, suggesting that beyond secreting mucus, goblet cells are infl ammatory eff ector cells.…”
Section: Secretion In Goblet-enriched Cellsmentioning
confidence: 64%
See 1 more Smart Citation
“…Although the HBE cells used in this study were from subjects without lung disease, it has been reported that bronchial epithelial cell cultures from subjects with asthma contain many more goblet cells and fewer ciliated cells compared with those from healthy subjects. 28 Conclusions Th e fi ndings in the current study suggest that sPLA 2 are released from ciliated airway epithelial cells and act on goblet cells in a paracrine manner to stimulate LTB 4 , LTC 4 , and MUC5AC secretion. We reported previously that IL-33 acts directly on goblet-enriched cells, but not ciliated-enriched cells, to stimulate IL-8 production, suggesting that beyond secreting mucus, goblet cells are infl ammatory eff ector cells.…”
Section: Secretion In Goblet-enriched Cellsmentioning
confidence: 64%
“…27,28 For the apical surface view, cultured HBE cell membranes were cut from the insert using a scalpel and were fi xed in 3% formaldehyde. For the z-stack view, the cell membrane was embedded in Tissue-Tek OCT Compound (Sakura FineTechnical Co Ltd), frozen in liquid nitrogen, and stored at -80°C.…”
Section: Immunofl Uorescent Confocal Microscopy Analysismentioning
confidence: 99%
“…PBECs were obtained from healthy children undergoing elective surgery (n = 5) (42). The generation and characterization of WD-PBEC cultures were described previously and are outlined in SI Materials and Methods (21,43). Briefly, primary cells were expanded in collagen-coated flasks until almost confluent and then were transferred onto collagen-coated semipermeable (0.4-μm pore size, 12-mm diameter) membrane supports.…”
Section: Methodsmentioning
confidence: 99%
“…Under basal unstimulated conditions, we have previously demonstrated that cultures from asthmatic PBEC, PBEC(A), children contained significantly more goblet cells and fewer ciliated cells compared with those from normal PBEC, PBEC(N), children (16).…”
mentioning
confidence: 94%
“…We have established a 3D well-differentiated model of PBECs, which, we believe, mimics the bronchial epithelium in vivo (16). Under basal unstimulated conditions, we have previously demonstrated that cultures from asthmatic PBEC, PBEC(A), children contained significantly more goblet cells and fewer ciliated cells compared with those from normal PBEC, PBEC(N), children (16).…”
mentioning
confidence: 95%